1952
DOI: 10.1139/z52-002
|View full text |Cite
|
Sign up to set email alerts
|

DISEASE IN CODLING MOTH LARVAE PRODUCED BY SEVERAL STRAINS OF BACILLUS CEREUS

Abstract: This paper describes a bacteriological study of strains of Bacillzts cereus Frankland and Frankland producing disease in codling moth larvae and an investigation of their pathogenicity. Strains of the bacterium were pathogenic t o the codling moth by feeding or by injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1959
1959
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…Previous studies have indicated a possible correlation between phospholipase activity and the entomopathogenic properties of B. thuringiensis (Heimpel, 1955 ;Krieg, 1971 ;Stephens, 1952). Two phosphatidylcholine esterases are known to be encoded by PlcRregulated genes (Agaisse et al, 1999).…”
Section: Cytotoxic and Haemolytic Activities Are Controlled By Plcrmentioning
confidence: 99%
“…Previous studies have indicated a possible correlation between phospholipase activity and the entomopathogenic properties of B. thuringiensis (Heimpel, 1955 ;Krieg, 1971 ;Stephens, 1952). Two phosphatidylcholine esterases are known to be encoded by PlcRregulated genes (Agaisse et al, 1999).…”
Section: Cytotoxic and Haemolytic Activities Are Controlled By Plcrmentioning
confidence: 99%
“…Bacilltis cerezls Frankland and Franklancl, strain CRII1-3 (47), is mildly pathogenic to wax 1110th larvae by injection; the LDjo is about 1500. So as not to introduce living ~iiaterial into the larvae, the vaccine was prepared b \~ boiling a pliysiological saline suspension of B. cerezis (rods and spores) for $ hour.…”
Section: Immune Responses Of Wax Moth Larvae To Other Bacterial Antigensmentioning
confidence: 99%
“…These results may indicate tliat tlie antigen of B. cerezis is not enhanced in vaccinated wax moth blood, tliough the possibility that the methocl of preparation of the vaccine probably liad a ha]-mful effect 011 the antigen must not be overlooked; it was kno\v11 t.o be difficult to immunize rabbits wit11 lieat-killed cultures of B . cerezrs (47). For personal use only.…”
Section: Immune Responses Of Wax Moth Larvae To Other Bacterial Antigensmentioning
confidence: 99%
“…B. cereus can cause opportunistic food-borne gastroenteritis and local/systemic infections in immunocompromised humans (85). Both B. thuringiensis (with and without Cry toxins) and B. cereus strains are highly pathogenic when injected directly into the hemocoels of insect larvae, in which they cause lethal septicemia (46,82,86,96).…”
mentioning
confidence: 99%